Possible cognition changes in women with polycystic ovary syndrome: a narrative review - Marzieh Saei Ghare Naz; Fatemeh Alsadat Rahnemaei; Fahimeh Ramezani Tehrani; Fatemeh Sayehmiri; Vida Ghasemi; Mojdeh Banaei; Giti Ozgoli (Korean Society of Obstetrics and Gynecology, 2023)
Nowadays, polycystic ovary syndrome (PCOS) and cognitive dysfunction are major health problems among female. This narrative review aimed to investigate cognitive dysfunction in female with PCOS. English and Persian articles published in PubMed, Scopus, Web of Science, Google Scholar, PsycINFO, Scientific Information Database, and Cochrane Database of Systematic Reviews until May 2022 were searched. Sixteen studies involving 850 female with PCOS and 974 controls were assessed. In these studies, the association between biochemical factors and symptoms of PCOS and memory, attention, executive functioning, information processing speed, and visuospatial skills was evaluated. The literature review revealed the possible cognitive changes in female with PCOS. This study summarized the different aspects of cognitive function in female with PCOS due to medication, psychological problems (mood disorders caused by disease symptoms and complications), and biochemical markers, such as metabolic and sex hormone abnormalities. Considering the existing scientific gap regarding the possibility of cognitive complications in female with PCOS, further biological studies should be conducted to evaluate the potential mechanisms involved.